Determination of Elbow Laxity in a Sequential Soft-Tissue Injury Model: A Cadaveric Study. (4th April 2018) - Schnetzke, Marc; Bergmann, Moritz; Wegmann, Kilian; Müller, Lars-Peter; Grechenig, Stephan; Grützner, Paul-Alfred; Guehring, Thorsten
Abstract : Background: The objective of our study was to analyze, under fluoroscopy, joint angulation of uninjured elbows and elbows with distinct induced collateral ligament injury. Methods: Twelve elbow specimens were tested for varus and valgus joint angulation using 4 different examination methods (application of both varus and valgus stress by each of 2 examiners [Examiner 1 and Examiner 2] and application of 1 and 2 Nm of torque using a calibrated electric force scale) in 4 elbow positions (in full extension with 90° of supination and 90° of pronation, and in 30° of flexion with 90° of supination and 90° of pronation). Six elbow specimens were examined under varus stress at each of 5 sequential stages: (1) intact, (2) transection of the lateral ulnar collateral ligament (LUCL), (3) complete transection of the lateral collateral ligament complex (LCLC), (4) transection of the anterior aspect of the capsule (AC), and (5) transection of the medial collateral ligament (MCL). An additional 6 elbow specimens were examined under valgus stress at 5 sequential stages: (1) intact, (2) transection of the anteromedial collateral ligament (AML), (3) complete transection of the MCL, (4) transection of the AC, and (5) transection of the LCLC. Examinations under fluoroscopy were made to measure the joint angulation. Intraclass correlation coefficients (ICCs) were calculated. Results: Testing of the intact elbow specimen by both examiners showed a joint angulation of <5°. Transection of the LUCL led to a varus joint angulation of 4.3° to 7.0°, and transection of the AML resulted in a valgus joint angulation of 4.9° to 8.8°. Complete dissection of the respective collateral ligament complex resulted in a joint angulation of 7.9° to 13.4° (LCLC) and 9.1° to 12.3° (MCL), and additional transection of the AC led to a joint angulation of >20° in some positions in both the medial and the lateral series. Under varus stress, elbow dislocations occurred only after dissection of the LCLC+AC (26% of the examinations) and additional dissection of the MCL (59%). Under valgus stress, elbow dislocations occurred only after dissection of the MCL+AC (30%) and additional dissection of the LCLC (47%). Very good to excellent ICCs were found among Examiners 1 and 2 and the tests done with the standardized torques at stages 1 through 4. Conclusions: Dynamic fluoroscopy makes it possible to distinguish among different stages of collateral ligament injury of the elbow and therefore might be helpful for guiding treatment of simple elbow dislocations. Clinical Relevance: Assessment of collateral ligament injury with varus and valgus stress testing under fluoroscopy is an easily available method and is often used as the imaging modality of choice to determine the degree of elbow laxity. The technique and results described in this study should form the basis for additional clinical studies.